Massive extrapancreatic solid pseudopapillary neoplasm misdiagnosed as hepatic tumor: a case report and literature review - Guo, Jixu; Zhao, Qingjuan; Qin, Liting; Xie, Shengjie; Lu, Shiliu; Li, Baibei; He, Meilin; Xie, Linhong; Yu, Shuiping (Frontiers in Oncology, 2024)
Background Solid pseudopapillary neoplasms (SPNs) of the pancreas are uncommon, low-malignancy neoplasms. Moreover, the occurrence of extrapancreatic SPNs is rarely encountered. Case summary A 45-year-old female presented with a right upper abdominal mass and abdominal pain for 3 and 1 months as chief complaints, respectively. Initially, the patient was misdiagnosed with hepatocellular carcinoma based on her symptoms and results of physical and imaging examinations. Following multidisciplinary discussion and ruling out surgical contraindications, a decision was taken to proceed with surgical intervention. Interestingly, the tumor was found to originate from the retroperitoneum and had invaded the right half of the liver and the right wall of the inferior vena cava. The operation was uneventful, and the pathological findings confirmed the tumor as an extrapancreatic SPN. The patient remained asymptomatic after 15 months of follow-up. Conclusion Surgical treatment remains the preferred option for extrapancreatic SPN. The preoperative misdiagnosis also highlights the importance of accurate diagnosis and the development of appropriate treatment strategies for liver masses.